Sensing mitochondrial DNA stress in cardiotoxicity - Ding, Yang-Nan; Tang, Xiaoqiang (Trends in endocrinology and metabolism, 2023)
Cytoplasmic mitochondrial DNA (mtDNA) can trigger the interferon response to promote disease progression, but mtDNA sensing mechanisms remain elusive. Lei et al. have shown that Z-DNA binding protein1 (ZBP1) cooperates with cyclic GMP-AMP synthase (cGAS) to sense Z-form mtDNA and transmit mtDNA stress signals to promote diseases such as cardiotoxicity, providing an important piece of the mtDNA stress landscape. Cytoplasmic mitochondrial DNA (mtDNA) can trigger the interferon response to promote disease progression, but mtDNA sensing mechanisms remain elusive. Lei et al. have shown that Z-DNA binding protein1 (ZBP1) cooperates with cyclic GMP-AMP synthase (cGAS) to sense Z-form mtDNA and transmit mtDNA stress signals to promote diseases such as cardiotoxicity, providing an important piece of the mtDNA stress landscape.